Public Dissatisfaction, Youth Mobilisation, and Anti Establishment Sentiment: Explaining the Rise of the Rastriya Swatantra Party in Nepal - Adhikari, Binod; Nepal, Subhadra; Saud, Nar Bahadur (NPRC Journal of Multidisciplinary Research, 2026)
Background: Following Nepal’s political transition to a federal democratic republic, citizens expected accountable governance, institutional reform, and socio-economic development. However, persistent political instability, corruption allegations, and governance challenges have contributed to growing public dissatisfaction with traditional political parties. These conditions have created opportunities for alternative political actors to gain electoral support.Methods: This qualitative study employed semi-structured interviews, media analysis, and social media observation to examine factors contributing to support for the Rastriya Swatantra Party (RSP). Data were collected in Kathmandu during March–April 2025 from 30 participants originating from multiple districts of Nepal, including 17 in-depth interviewees and 13 participants providing shorter structured responses. Populism theory guided the analytical framework.Results: Findings reveal five interconnected drivers of support for alternative political forces: dissatisfaction with traditional political parties, youth political awakening, anti-elite sentiment, institutional distrust, and the influence of digital media. Participants also linked migration-related frustrations and perceptions of corruption to growing support for political reform and alternative leadership. The September 2025 youth mobilisation movement was frequently identified as a catalyst for increased political awareness and civic engagement.Conclusion: The rise of the RSP reflects broader transformations in Nepal’s democratic landscape shaped by generational change, institutional distrust, and demands for governance reform. Youth mobilisation and digital communication have become increasingly influential in shaping political participation and electoral behaviour.Novelty: This study contributes to emerging scholarship on political transformation in Nepal by examining the relationship between youth mobilisation, anti-establishment sentiment, and support for alternative political actors through qualitative evidence from diverse voter perspectives.